The snap-through stability of plastically designed steel pitched-roof portal frames - Bryant, John Spencer (My University, 2015)
Recent proposed rafter slenderness limits, to prevent snap-through of plastically designed pitched-roof portal frames, incorporate the elastic snap-through buckling load of such frames. It has been suggested that the elastic snap-through buckling load used in the proposals is over-estimated making these slenderness limits unconservative. This is supported by a more rigorous elastic analysis. To test the proposals, model frames lying on or close to the slenderness limits were tested to failure in the laboratory. Frame dimensions were chosen so that the frames were only susceptible to snap-through instability. Failure loads far lower than the expected plastic collapse loads were measured, showing that the elastic snap-through buckling load is over -estimated . Since plastic analysis is easily applied to portal frames, these slenderness limits are best replaced by a similar limit incorporating a more accurate elastic snap-through buckling load. A new limit is outlined which must still be tested by further research
Keywords: Roofing; Structural frames; Roofs--Design and construction